Aged human skin accumulates mast cells with altered functionality that localize to macrophages and vasoactive intestinal peptide‐positive nerve fibres. (1st April 2019) - Pilkington, S.M.; Barron, M.J.; Watson, R.E.B.; Griffiths, C.E.M.; Bulfone‐Paus, S.
Summary: Background: Skin health declines with age and this is partially attributed to immunosenescence. Mast cells (MCs) are innate immune cells that coordinate tissue immune responses integral to skin homeostasis and disease. Objectives: To understand how MCs contribute to human skin ageing, we investigated how intrinsic ageing impacts MC phenotype and MC relationships with other immune cells and skin structures. Methods: In photoprotected skin biopsies from young (≤ 30 years) and aged (≥ 75 years) individuals, immunostaining and spatial morphometry were performed to identify changes in MC phenotype, number, distribution and interaction with the vasculature and nerve fibres. Quantitative polymerase chain reaction was used to measure changes in gene expression related to immune cell activity and neuropeptide signalling. Results: Skin MCs, macrophages and CD8 + T cells increased in number in intrinsically aged vs. young skin by 40%, 44% and 90%, respectively ( P < 0·05), while CD4 + T cells and neutrophils were unchanged. In aged skin, MCs were more numerous in the papillary dermis and showed a reduced incidence of degranulation (50% lower than in young, P < 0·01), a conserved tryptase–chymase phenotype and coexpression of granzyme B. In aged skin, MCs increased their association with macrophages ( 48% vs. 27%, P < 0·05) and nerve fibres ( 29% vs. 16%, P < 0·001), while reducing their interactions with blood vessels ( 34% vs. 45%, P < 0·001). Additionally, we observed modulation of gene expression of vasoactive intestinal peptide (VIP; increased) and substance P (decreased) with age; this was associated with an increased frequency of VIP + nerve fibres (around three times higher in aged skin, P < 0·05), which were strongly associated with MCs ( 19% in aged vs. 8% in young, P < 0·05). Conclusions: In photoprotected skin we observed an accumulation of MCs with increasing age. These MCs have both altered functionality and distribution within the skin, which supports a role for these cells in altered tissue homeostasis during ageing.